Sustainable urban logistics concepts: A collaborative design approach considering stakeholder perspectives - Robert Teschendorf; Maximilian Engelhardt; Birte Malzahn; Markus Husemann; Christian Butz; Stephan Seeck (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Goods flows in cities increase due to urbanization and growing e-commerce. Deliveries become more fragmented and more difficult to consolidate and control. This leads to an ever-increasing strain on urban infrastructure and logistics systems. With our work, we aim to design a stakeholder-oriented urban logistics concept to improve sustainability and relieve urban infrastructure. Methodology: We chose a design thinking approach augmented by proven scientific methods. First, we analyzed the requirements of urban logistics stakeholders by conducting both a literature review and twenty-one qualitative interviews. Second, we carried out ideation workshops with different stakeholder groups to elaborate new solutions for urban goods flows. Findings: The findings offer deep insights into urban logistics stakeholders' challenges, requirements and wishes and outline a clear point of reference for the development of sustainable urban logistics concepts. The results show stakeholders' strong focus on consolidation, on intermodal transport and on a better connectivity between relevant IT applications as well as a strong interest in autonomous transportation systems. Originality: The work evaluates innovative urban logistics concepts empirically that have not yet been developed, designed or further investigated in this combination before. Thus, numerous opportunities for further work using modelling, simulation or field-testing are offered.
urn:nbn:de:gbv:830-882.0200713; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; City Logistics